Short-term and long-term outcomes of critically ill patients with solid malignancy: a retrospective cohort study - Su Yeon Lee; Jin Won Huh; Sang-Bum Hong; Chae-Man Lim; Jee Hwan Ahn (The Korean Journal of Internal Medicine)
Background/Aims With the global increase in patients with solid malignancies, it is helpful to understand the outcomes of intensive care unit (ICU) admission for these patients. This study evaluated the risk factors for ICU mortality and the short-and long-term outcomes in patients with solid malignancies who had unplanned ICU admission. Methods This retrospective cohort study included patients with solid malignancies treated at the medical ICU of a single tertiary center in South Korea between 2016 and 2022. Results Among the 955 patients, the ICU mortality rate was 23.5%. Lung cancer was the most common cancer type (34.2%) and was significantly associated with increased ICU mortality (odd ratio [OR] 1.58, p = 0.030). Higher Sequential Organ Failure Assessment scores at ICU admission (OR 1.11, p < 0.001), the need for mechanical ventilation (OR 6.74, p < 0.001), or renal replacement therapy during the ICU stay (OR 2.49, p < 0.001) were significantly associated with higher ICU mortality. The 1-year survival rate after ICU admission was 29.3%, with a median survival of 37 days for patients requiring mechanical ventilation, and 23 days for patients requiring renal replacement therapy. Conclusions This study showed that critically ill patients with solid malignancies had poor 1-year survival despite relatively low ICU mortality. These findings highlight the need for careful consideration of ICU admission in patients with solid malignancy, and decision-making should be based on an understanding of the expected short- and long-term prognosis of ICU admission after an informed discussion among patients, families, and physicians.